Pengaruh Model Pembelajaran Problem Based Learning (PBL) berbantuan Double Diamond terhadap Kemampuan Pemecahan Masalah pada Mata Pelajaran Ekonomi - Devi Anatasya; Rendra Gumilar; Kurniawan Kurniawan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
. The problem in this research is the low level of students' problem solving skill in economics subjects. This research was conducted to determine the effect of the Problem Based Learning (PBL) model assisted by Double Diamond in improving students' problem solving skill in economics subjects. This research uses a quasiexperimental method with a Nonequivalent Pretest-Posttest Control Group Design. Data collection techniques use tests and interviews. The population in this study was all class X students with a total of 269 students. The samples used in this research were class X-3 and X-1 which were taken using purposive sampling technique. The results of the research show that there is a difference in the increase in students' problem solving skill between the experimental class which uses the Problem Based Learning (PBL) model assisted by Double Diamond and the control class which uses the Discovery Learning model. This study shown by the average posttest score for the experimental class of 68.826 while the control class was 56.582. Based on the average N-Gain for the experimental class, it was 0.5212, while the control class obtained a value of 0.2913. Apart from that, the Independent Samples T-Test shows a Sig-2 Tailed value of 0.000 < 0.05, which shows that Ho is rejected and Ha is accepted.